EMPA-REG OUTCOME trial and Canagliflozin Cardiovascular Assessment Study: Looking beyond the obvious - Rishad Ahmed; Pallavi Kawatra (Wolters Kluwer Medknow Publications, 2017)
With the addition of sodium-glucose cotransporter-2 inhibitors to the current arsenal of oral antidiabetics (OAD), a lot has changed. From questioning their glucouretic mechanism to understanding their pleiotropic effects, it has been an eventful journey. In 2008, after the rosiglitazone fiasco, the US Food and Drug Administration (FDA) mandate was passed to ensure the safety of the OAD. Up to the gliptins, there was an era of cardiovascular (CV) safety which progressed to CV protection with the EMPA-REG OUTCOME trial. It came with a lot of questions regarding the probable mechanism and the doubts of whether it will translate into a class effect or not. After the Canagliflozin CV Assessment Study results, a lot of things have come into light regarding the overall benefits with these molecules. This review highlights the similarities and dissimilarities in the two trial results.